Research priorities on ending child marriage and supporting married girls - Svanemyr, Joar (Reprod Health, 2015)
Over the past few years the issue of child marriage has received growing political and programmatic attention. In spite of some progress in a number of countries, global rates have not declined over the past decade. Knowledge gaps remain in understanding trends, drivers and approaches to ending child marriage, especially to understand what is needed to achieve results on a large scale. This commentary summarizes the outcomes of an Expert Group Meeting organized by World Health Organization to discuss research priorities on Ending Child Marriage and Supporting Married Girls. It presents research gaps and recommends priorities for research in five key areas; (i) prevalence and trends of child marriage; (ii) causes of child marriage (iii) consequences of child marriage; (iv) efforts to prevent child marriage; (v) efforts to support married girls.